The Next 500 Years : Life in The Coming Millennium - Berry, Adrian (London Headline, 1995)
A futuristic prediction of possible events over the next five decades, which explores potential scientific and technological advances and developments and suggests what life will be like in the year 2500. Covers a wide range of topics and issues, such as transport, food, military developments and space.
Include Index, Glossary, References, Notes, Bibliography and Appendix
Keywords: Astronautics and civilization -- Forecasting -- Science--Forecasting